(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Procuratorate "Latin procurare-mano" to care in some countries, for example: France, Sweden, Germany, as state in states, inciting criminal cases, favoring prosecution, State in judicial proceedings as a special state body entrusted with the powers to protect interest’s tariff. [1]